The electric vehicle shortest path problem with time windows and prize collection - Cassia, Antonio; Jabali, Ola; Malucelli, Federico; Pascoal, Marta (2022 17th Conference on Computer Science and Intelligence Systems (FedCSIS), 2022)
The Electric Vehicle Shortest Path Problem (EVSPP) aims at finding the shortest path for an electric vehicle (EV) from a given origin to a given destination. During long trips, the limited autonomy of the EV may imply several stops for recharging its battery. We consider combining such stops with visiting points of interest near charging stations (CSs). Specifically, we address a version of the EVSPP in which the charging decisions are harmonized with the driver's preferences. The goal is to maximize the total gained score (assigned by the driver to the CSs), while respecting the time windows and the EV autonomy constraints. We define the problem as a MILP and develop an A* search heuristic to solve it. We evaluate the method by means of extensive computational experiments on realistic instances.